Water from the Heights, Water from the Grassroots : The Governance of Common Dynamics and Public Services in La Paz-El Alto - Botton, Sarah; Hardy, Sébastien; Poupeau, Franck (World Bank, Washington, DC, 2017)
In this paper, the authors approach water governance not only through the prism of sectoral organization and the official services, but also through all of the practices, still to be “integrated” into the regulatory framework,that give rise to order and social progress. In doing so, we do not wish to limit public actions tog overnment decisions, however much these may have been democratically debated or even jointly constructed, but rather we wish to re-articulate social practices and collective action. consider that what society produces for itself is an integral part of governance. For this, start with the example of access to urban water in Bolivia, as that public action in Bolivia and the water sector not only emblemize what is being played out on the regulation front between State, communities, and society, but also question the place that the collective interest holds within the sphere of general interest. Firstly, the political project of Evo Morales, Bolivia’s first Aymara president and a defender of the country’s traditional values, was to redefine the rules of the game in view of reappropriating a national identity. The intent was to make them less liberal and more inclusive, notably by attempting to integrate the dynamics of customary practice into the workings of the modern State. Moreover, his policies have largely been based on the re-appropriation of national resources, in a broadand highly symbolic move to negotiate with the multinationals that manage the country’s water, gas and oil industries. Secondly, the water sector lends itself particularly well to an analysis of multi-stakeholder governance as the reality of large cities in developing countries is still one where limited or failing public services struggle to serve agglomerations and keep up with the pace of their demographic growth. Public water distribution services (managed by the State or delegated to the private sector) are thus systematically “supplemented” informally by a multitude of other players whose social function is crucial: small private traders, itinerant or network operators, community services (cooperatives or user associations), resale by neighbors, etc. These stakeholders participate in water governance even if they are not part of the sector’sregulatory framework. After setting up a panorama of the official urban water sector in La Paz-El Alto, two cases that typify the thinking on the way that the dynamics of the commons and public service are interlinked : one involves the environmental risks and possible trade-offs required to balance the interests of communities and the general interest, while the other concerns the issues of articulating grassroots common services (water cooperatives) and public service.